2002
DOI: 10.1046/j.1439-0434.2002.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Integrating Planting Time, Fungicide Application and Host Resistance on Potato Late Blight Development in South‐western Uganda

Abstract: The presence of inocula all year round poses a daunting challenge to the management of late blight [causal agent Phytophthora infestans (Mont.) De Bary] of Solanum potato in the highlands of eastern Africa. Commercial production depends heavily on use of fungicides and, to some extent, host resistance. In this study, integration of host resistance and fungicide application reduced late blight severity by more than 50% and resulted in yield gains of more than 30% when compared with the untreated control. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
5
8
0
1
Order By: Relevance
“…It was, therefore, necessary to select a variety which can give high tuber yield and resistant to late blight. For commercial production of Irish potato, Kankwatsa et al (2002) suggested that use of resistant varieties reduced the late blight severity by more than 50% and resulted in yield gains of more than 30%, in the present study the variety Belete gave high tuber yield and tolerant to late blight.…”
Section: Discussionsupporting
confidence: 55%
“…It was, therefore, necessary to select a variety which can give high tuber yield and resistant to late blight. For commercial production of Irish potato, Kankwatsa et al (2002) suggested that use of resistant varieties reduced the late blight severity by more than 50% and resulted in yield gains of more than 30%, in the present study the variety Belete gave high tuber yield and tolerant to late blight.…”
Section: Discussionsupporting
confidence: 55%
“…This is in accordance with the findings of Samucha and Cohen (1986) who claimed better effect of the systemic and contact fungicides to control late blight of potato. For commercial production of potato Kankwasta et al, (2002) suggested that mancozeb application reduced the late blight severity more than 50% and increased yield more than 30%. De and Mohasin (1999) stated that Mancozeb gave the lowest disease incidence and highest yield and greatest net benefit against late blight.…”
Section: Resultsmentioning
confidence: 99%
“…No entanto, a PT foi maior do que no cultivo de primavera (Tabela 2), no qual praticamente não houve incidência de requeima. KANKWATSA et al (2002), após realizar experimentos para verificar a interação entre época de cultivo, aplicação de fungicidas e resistência de clones de batata à requeima, concluiu que a melhor resposta de produtividade em relação à aplicação de fungicidas ocorreu quando a requeima foi mais severa e a produtividade não depende somente do controle da requeima, mas de fatores como a constituição genética. Isso explicaria porque os clones Macaca e SMINIA793101-3, mesmo sendo severamente atacados pela requeima, produziram mais do que o clone SMIJ461-1 no outono de 2007.…”
Section: Resultsunclassified